Working, Housekeeping and Organizing: The Patriarchal System in Three Women’s Living Spaces - Tjandraningsih, Indrasari (Yayasan Jurnal Perempuan, 2018)
This paper discusses women's labor activities in trade union and the obstacles they encounter. The discussion focuses on the three roles caried out by women factory workers in domestic space as mothers and wives and in public space as laborers as well as activists of labor organizations. The information in this paper derived from observations of women factory workers’ activities in union organization and two ethnographic books on factory workers’ resistance. The subject was chosen because for more than two decades there was no significant changes in the position of women in the labor movement. The research questions of this paper are what are the obstacles for women workers to work and organize like male workers? Why are male workers so dominant, even in industries where the workforce is mostly women? How can women play the role as mothers, as workers and as leaders of labor organizations? The results of the analysis show the role and stereotype of gender in patriarchal societies within labor organizations is a barrier for women to become a significant player in the labor movement. However, strong determination for women to fight injustice supported by personal qualities proves that women are able to perform in the triple activities all at once.